Treatment of Feline Panleukopenia Virus Disease at Miracle Animal Clinic, Surabaya - Lailia Dwi Kusuma Wardhani; Indra Rahmawati; Arief Mardijanto; Yoakim Hardiputra Ngabut (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2023)
Feline Panleukopenia Virus (FPV) is a viral disease caused by the Parvoviridae family. FPV can attack cats, especially young felidae. FPV has high morbidity and mortality. The aim of this study was to find a treatment of Feline Panleukopenia Virus at Mircale Animal Clinic Surabaya. The research was conducted in February 2022. The results showed that there were 8 cats with positive FPV test kit result. All of cats had sama clinical sign include vomiting, diarrhea and anorexia Treatment of Feline Panleukopenia Virus at Mircale Animal Clinic Surabaya through administration of fluid therapy, antacids, anti-inflammatories, B complex vitamins and antibiotics. Prevention of FPV through vaccination, sanitation, and environmental hygiene. Keywords: Feline Panleukopenia Virus, Treatment, Miracle Animal Clinic Surabaya